Global epidemiology of TB - Glaziou, Philippe (Henry Stewart Talks, 2013)
Tuberculosis, Epidemiology, Incidence, Prevalence, Mortality, Case fatality, TB drug resistance, HIV-associated TB, Progress in TB control, Impact of TB control, TB elimination